Proces rozšiřování ve vztazích Ruské federace a Organizace Severoatlantické smlouvy - Laru, Dmitry (Univerzita Karlova, Fakulta sociálních věd, 2015)
This particular work deals with the process of expansion by the North Atlantic Alliance in view of the theory of balance of power and the relationship between Russia and NATO. The author of the work draws on assumption that NATO's expansions, that have followed the end of the cold war, strengthen NATO's might, to which Russia must react to counter the growing power of the potential adversary. This work is divided into two main thematic parts. The first part regards the three waves of the expansion which followed the breakup of the Soviet Union (1999, 2004, and 2009); therein, the author analyzes NATO's strengthening on the military, political and geopolitical levels. The second part of the work is devoted to unveiling of Russia's potential counterbalancing steps. The Russian attempt to counterbalance the NATO's moves, of course, has also been analyzed within three frames - military, political and geopolitical. The analysis of the counterbalancing by Russia, as well as the strengthening of NATO is presented within the frame defined by five year periods. To facilitate the theoretical view, the power counterbalancing analyses has been divided into, so called, "Hard balancing" and "Soft balancing". Because the end of the bipolar conflict contributed to substantial changes in international political. Práce se zabývá rozšiřovacím procesem Severoatlantické aliance ve vztahu Ruska a NATO z perspektivy teorie rovnováhy moci. Autor vychází z předpokladu, že rozšiřovací proces po konci studené války způsobuje posílení NATO, na což Rusko musí reagovat vyvažováním vůči rostoucí moci potenciálního nepřítele. Práce je rozdělena na dvě hlavní tematické části. V té první jsou analyzovány tři rozšiřovací vlny po rozpadu Sovětského svazu (1999, 2004, 2009), přičemž autor analyzuje posílení NATO na vojenské, politické a geopolitické úrovni. Druhá část práce je věnována odhalování potenciálních vyvažovacích kroků Ruska, přičemž ruské vyvažování je taktéž analyzováno v rámci tří dimenzí - vojenské, politické a geopolitické. Analýza ...